Chromatin remodeling enzyme Snf2h regulates embryonic lens differentiation and denucleation - He, Shuying; Limi, Saima; McGreal, Rebecca S; Xie, Qing; Brennan, Lisa A; Kantorow, Wanda Lee; Kokavec, Juraj; Majumdar, Romit; Hou, Harry; Edelmann, Winfried; Liu, Wei; Ashery-Padan, Ruth; et al. (Development (Cambridge, England), 2016)
Ocular lens morphogenesis is a model for investigating mechanisms of cellular differentiation, spatial and temporal gene expression control, and chromatin regulation. Brg1 (Smarca4) and Snf2h (Smarca5) are catalytic subunits of distinct ATP-dependent chromatin remodeling complexes implicated in transcriptional regulation. Previous studies have shown that Brg1 regulates both lens fiber cell differentiation and organized degradation of their nuclei (denucleation). Here, we employed a conditional Snf2h(flox) mouse model to probe the cellular and molecular mechanisms of lens formation. Depletion of Snf2h induces premature and expanded differentiation of lens precursor cells forming the lens vesicle, implicating Snf2h as a key regulator of lens vesicle polarity through spatial control of Prox1, Jag1, p27(Kip1) (Cdkn1b) and p57(Kip2) (Cdkn1c) gene expression. The abnormal Snf2h(-/-) fiber cells also retain their nuclei. RNA profiling of Snf2h(-/) (-) and Brg1(-/-) eyes revealed differences in multiple transcripts, including prominent downregulation of those encoding Hsf4 and DNase IIβ, which are implicated in the denucleation process. In summary, our data suggest that Snf2h is essential for the establishment of lens vesicle polarity, partitioning of prospective lens epithelial and fiber cell compartments, lens fiber cell differentiation, and lens fiber cell nuclear degradation.
Keywords: Denucleation; autofagie; Cell Cycle; epitelové buňky; buněčné jádro; jaderné proteiny; DNA-Binding Proteins; Cell Differentiation; transkripční faktory tepelného šoku; DNA Helicases; Nuclear Proteins; vývojová regulace genové exprese; mitofagie; transkriptom; Autophagy; Epithelial Cells; kompartmentace buňky; chromozomální proteiny, nehistonové; mutace; Smarca5; Snf2h; DNA-helikasy; oční čočka; Transcription Factors; Smarca4; Transcriptome; Terminal differentiation; myši knockoutované; buněčný cyklus; Brg1; Gene Expression Regulation, Developmental; Models, Biological; transkripční faktory; Cell Nucleus; ženské pohlaví; PAX6 Transcription Factor; Mutation; zvířata; Lens; Embryo, Mammalian; restrukturace chromatinu; biologické modely; Chromosomal Proteins, Non-Histone; Cell Compartmentation; Lens, Crystalline; embryo savčí; Mice, Knockout; Mitophagy; DNA vazebné proteiny; Adenosine Triphosphatases; Chromatin Assembly and Disassembly; buněčná diferenciace; Heat Shock Transcription Factors; Female; Cataract; adenosintrifosfatasy; transkripční faktor PAX6; Animals